Metabolic regulation of obesity by naturally occurring compounds: mechanisms and therapeutic potential - Das, Mousumi; Yagnik, Unnati; Raninga, Ishita; Banerjee, Debashis (Frontiers in Endocrinology, 2025)
The global obesity epidemic continues to escalate, driving demands for safer and more effective therapeutic strategies. This review evaluates the potential of natural bioactive compounds as multi-targeted interventions for obesity management. Plant-derived polyphenols (e.g., epigallocatechin-3-gallate (EGCG), resveratrol), alkaloids (e.g., berberine), and marine carotenoids (e.g., fucoxanthin) demonstrate remarkable capacity to modulate fundamental obesity pathways through (A) suppression of adipogenesis via PPARγ and C/EBPα inhibition, (B) activation of lipolysis through hormone-sensitive lipase (HSL) stimulation and AMPK phosphorylation, (C) enhancement of thermogenesis via UCP1 upregulation, and (D) gut microbiome modulation through SCFA production. Clinical evidence supports the efficacy of selected compounds, with green tea catechins showing 4% to 5% body fat reduction and berberine demonstrating significant metabolic improvements. These natural agents offer distinct advantages over conventional drugs through their pleiotropic mechanisms and favorable safety profiles. However, bioavailability limitations and inter-individual variability present significant challenges. Innovative delivery systems, including nanoencapsulation and phospholipid complexes, show promise to enhance the therapeutic potential. The review highlights emerging strategies combining microbiome modulation with precision nutrition approaches while emphasizing the need for standardized clinical protocols. By bridging ethnopharmacological knowledge with modern scientific validation, natural compounds represent a promising avenue to develop sustainable, multi-targeted anti-obesity therapies that address both physiological and metabolic aspects of this complex disorder.